Paravertebral Block Combined with Sedation for a Myasthenic Patient Undergoing Breast Augmentation - Betul Kozanhan; Betul Basaran; Leyla Kutlucan; Sadık Ozmen (Case Reports in Anesthesiology)
Paravertebral block is a unilateral analgesic technique that can provide adequate surgical anesthesia and great advantages in many types of surgery with a low side-effect profile. In this case we present combination of bilateral thoracic paravertebral block under ultrasound guidance with sedation which provides complete anesthesia and postoperative analgesia in a myasthenic patient undergoing cosmetic breast surgery. In myasthenic patients paravertebral blocks may be a better option for breast surgery with avoiding the need for muscle relaxants and opioids and risk of respiratory failure in postoperative period.